Dampak Psikologis Korban Inses: Analisis Terhadap Kualitas Hidup dan Fungsi Sosial dalam Pendekatan Empiris Normatif - Hawa Hidayatul Hikmiyah; Ahmad Riski Musthofa; Amal Zainun Naim (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – This study aims to analyze the ways in which psychological impacts can affect the quality of life and social functioning of incest victims, both in the short and long term, through the adoption of a normative empirical approach. Methods – The research methodology employed in this empirical-normative approach entails a systematic and comprehensive process aimed at delving into the multifaceted psychological repercussions experienced by incest victims. The empirical-normative approach, characterized by a meticulous examination of community cases juxtaposed with pertinent legal frameworks, elucidates the profound psychological ramifications endured by victims. Initiating this methodology involves meticulously selecting a diverse array of representative case studies from a community. This selection process may entail collaborative efforts with various stakeholders such as child protection agencies, mental health services, or non-governmental organizations specializing in aiding incest victims, thereby ensuring the identification of pertinent cases. The overarching goal is to gain profound insights into the intricacies of victims’ experiences and the profound psychological impacts they have undergone. Findings – Research findings indicate that individuals subjected to incest commonly endure protracted trauma, precipitating a spectrum of symptoms, encompassing withdrawal, overwhelming guilt, diminished self-worth, impaired socialization, and pervasive social detachment. Furthermore, victims may manifest additional symptoms including mood fluctuations, withdrawal tendencies, heightened stress, profound depression, and challenges in interpersonal communication. Socially, incest survivors frequently confront pervasive stigma and discrimination within the familial and societal spheres, undermining the fundamental constructs of familial bonds and child welfare. Research implications – The theoretical implications derived from these findings underscore the importance of comprehensive and well-coordinated interventions. Such interventions should encompass psychological support, educational initiatives, and robust child-protection measures. Additionally, preventive endeavors targeting heightened public awareness regarding incest and extending support to victims are pivotal in effectively addressing profound psychological repercussions. Originality/value – This research significantly enhances society's comprehension of the intricate nature and pressing urgency surrounding the issue of incest, underscoring the necessity for a multidisciplinary approach to effectively tackle the socio-psychological impact on children victimized by incest.